Initiating psychoanalysis : perspectives - Reith, Bernard, 1954- (New York : Routledge, 2012)
'Initiating Psychoanalysis presents an international collection of papers brought together by the Working Party on Initiating Psychoanalysis of the European Psychoanalytic Federation and addresses the specific clinical and technical issues involved in launching the processes that are at the core of psychoanalysis and psychoanalytic treatment. Expert contributors provide introductions and commentaries on a selection of psychoanalytic papers, including one by Freud himself, which refer to beginning psychoanalytic treatment in a wide range of settings. Divided into four main sections areas of discussion include: - historical and conceptual developments in the field - practical, technical and ethical considerations - unconscious transference and counter-transference dynamics of initial interviews - internal factors that can help or hinder the psychoanalyst in his work to initiate psychoanalysis. This book will be helpful to all psychoanalytical practitioners in thinking about their work in first interviews with prospective patients, as well as psychoanalysts and psychotherapists at all levels of experience, who will be able to use this book to enrich their own practice'--
Includes bibliographical references.
Keywords: Psychoanalysis -- Methodology; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health